Bacillus pumilus probiotic feed supplementation mitigates Lawsonia intracellularis shedding and lesions - Tanja Opriessnig; Anbu K. Karuppannan; Dana Beckler; Tahar Ait-Ali; Ana Cubas-Atienzar; Patrick G. Halbur (Veterinary Research, 2019)
Abstract The causative agent of ileitis, Lawsonia intracellularis, is commonly associated with diarrhea and reduced weight gain in growing pigs. The effect of in-feed probiotics on L. intracellularis infection dynamics was evaluated. In brief, 70 2.5-week-old-pigs were randomly divided into six groups with 10–20 pigs each. All pigs were fed an age appropriate base ration for the duration of the study, which was supplemented with one of three Bacillus strains including B. amyloliquefaciens (T01), B. licheniformis (T02) and B. pumilus (T03). Another group was orally vaccinated with a commercial live L. intracellularis vaccine (VAC) at 3 weeks of age. At 7 weeks of age, T01-LAW, T02-LAW, T03-LAW, VAC-LAW and the POS-CONTROL groups were challenged with L. intracellularis while the NEG-CONTROL pigs were not challenged. All pigs were necropsied 16 days later. By the time of inoculation, all VAC-LAW pigs had seroconverted and at necropsy 10–65% of the pigs in all other challenged groups were also seropositive. The results indicate a successful L. intracellularis challenge with highest bacterial DNA levels in POS-CONTROL pigs, VAC-LAW pigs and T01-LAW pigs. There was a delay in onset of shedding in T02-LAW and T03-LAW groups, which was reflected in less severe macroscopic and microscopic lesions, reduced intralesional L. intracellularis antigen levels and a lower area under the curve for bacterial shedding. Under the study conditions, two of the probiotics tested suppressed L. intracellularis infection. The obtained findings show the potential of probiotics in achieving antibiotic-free control of L. intracellularis.